1985
DOI: 10.1152/ajprenal.1985.248.5.f656
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial regulation of renal hemodynamics: role of pancreatic glucagon

Abstract: The aim of this study was to ascertain the quantitative importance of glucagon in mediating protein-induced increases in renal blood flow (RBF) and glomerular filtration rate (GFR) during the postprandial state. Six chronically instrumented conscious dogs were each subjected to four protocols: normal protein control meal (C); high protein meat meal (M); somatostatin infusion and meat (S + M); and glucagon infusion. C produced small increases in RBF (12 +/- 2%) and GFR (14 +/- 2%) without changing arterial plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 0 publications
3
46
0
Order By: Relevance
“…9,25 Glucagon is believed to be responsible for increased GFR after a high-protein meal or the glomerular hyperfiltration seen in early stages of diabetes. 10 Although MCs may, therefore, represent a major target of glucagon in the glomerulus, it remains unclear whether glucagon has a direct effect on MCs or the signaling mechanism(s) involved. The present study provides evidence that MCs express functional glucagon receptors.…”
Section: Discussionmentioning
confidence: 99%
“…9,25 Glucagon is believed to be responsible for increased GFR after a high-protein meal or the glomerular hyperfiltration seen in early stages of diabetes. 10 Although MCs may, therefore, represent a major target of glucagon in the glomerulus, it remains unclear whether glucagon has a direct effect on MCs or the signaling mechanism(s) involved. The present study provides evidence that MCs express functional glucagon receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is still no consensus as to the intrarenal vascular sites of action of adenosine. Glu cagon has also been noted as an endogenous regulator of renal hemodynamics, especially at the postprandial state (7). We reported that intrarenal administration of glucagon in creased RBF and GFR proportionally, in dicating the preferential dilation of the afferent arteriole (8,9).…”
mentioning
confidence: 81%
“…Several studies have established that this hormone participates in, or is even indispensable for, the postprandial increase in GFR (6)(7)(8)(9)(10)(11). However, this effect of glucagon is probably indirect and involves other mediators (12) because the plasma concentration of glucagon required to increase GFR exceeds the usual peripheral concentration seen after a protein meal (6,10,13). Moreover, direct infusion of glucagon into the renal artery fails to increase GFR in dogs (10,14), humans (8), and rats (Ahloulay, M., personal observation).…”
Section: Introductionmentioning
confidence: 99%